RESIDUE ANALYSIS IN VANNAMEI SHRIMP (Litopenaeus vannamei) AQUACULTURE IN TUBAN REGENCY - Putri, Ardiani Utomo; Yudasmara, Gede Ari; Prasetia, I Nyoman Dodik (Jurusan Perikanan dan Kelautan, 2025)
Food safety is a crucial aspect of vannamei shrimp (Litopenaeus vannamei) aquaculture, particularly regarding the use of chemicals that may leave harmful residues. This study aims to analyze the compliance of chemical usage in vannamei shrimp farming in Tuban Regency with food safety standards. Data were collected through interviews with farmers and fish health analysts, as well as laboratory testing of shrimp samples from several pond locations. The analysis results showed that all samples from the tested sites were compliant, meaning they met the permitted residue limits. Therefore, it can be concluded that shrimp farming practices in this region have been carried out responsibly and in accordance with prevailing safety standards. This study may serve as a reference for the development of guidance and monitoring efforts toward sustainable shrimp farming in other regions.